Penerapan Hukum Responsif terhadap Tindak Pidana Korupsi Studi Kasus Putusan Nomor: 56/PID.SUS-TPK/2017/PN.KPG - Radja, Valentri Marlita (Penerbit Goodwood, 2024)
Purpose: This study aims to examine law enforcement against corruption in Indonesia from a responsive legal perspective, in response to the ongoing concern over corruption’s widespread impact on national integrity. Thus, this study seeks to evaluate whether existing judicial practices reflect the participatory and contextual principles inherent in responsive law, using a specific case decision as a focal point. Research Methodology: This study employs a normative juridical approach, focusing on legal norms and principles. This is supported by a document study that specifically analyzes Decision Number: 56/Pid. Sus-TPK/2017/PN.Kpg, to assess how judicial reasoning aligns with the responsive legal framework. Results: The analysis reveals that the court’s decision in this case does not fully embody the core values of the responsive law. In particular, it lacks sufficient public participation and does not address the restoration of social justice for communities affected by corruption. Judgments tend to focus on procedural legality rather than the broader societal impact and justice. Conclusion: The study concludes that current corruption law enforcement in Indonesia, as exemplified by the case analyzed, remains largely formalistic. To improve outcomes and public trust, a shift toward a responsive legal approach is necessary, one that emphasizes substantive justice, societal values, and community involvement. Limitations: This study is limited to the analysis of one court decision and does not encompass empirical field data or a broader range of judicial cases. Contribution: This study contributes to the discourse on judicial reform by highlighting the gap between legal decisions and responsive law principles.